The Impacts of Online Communities in the Perspective of Institutional Marketing (Journal of Informatics and Mathematical Sciences, 2017)
Social web promotes word-of-mouth communication on products and services. The use of social media in marketing for educational institutions is important, considering that education is a public good and marketing its products or services can enhance their good name and proceeds. Social media sites are basically related to collaboration among communities, community formation, and bridging communities. These communities are interlinked, and a member made comments either favorable or unfavorable on diverse shared posts and play an important role for brand image. In an institution of education, the phenomenon of social media marketing is new and has rarely been taken to inspect. The present research is conducted to inquire the influence of online communities on institutional online marketing. The main objective of the current study is to examine the impact of student online communities on university online promotional activities This study examines the influences of community attachment, community involvement, perceived benefits and perceived cost in order to explore in what way these concepts influence university online marketing or promotional activities Using social exchange theory as theoretical fireworks and based on the data collected from online communities, this study made evident that community attachment and perceived benefits are the significant factors that positively influence community members to support university online promotional activities. Furthermore, study limitations and future directions are also discussed.
Keywords: Social Media; Social media marketing; Universities; student online communities